Auricular keloids: a literature review - Flores García, Edgar Alexis; Escobedo Fernandez, Yessenia; Hinojosa Rodriguez, Jose Martin; Parra Enciso, Rebeca Pamela; Mancillas Solis, Gerardo Alberto; Morales Lazo, Rafael Andres; Hermosíllo Venegas, Jennifer; Burciaga Castaneda, Ricardo; Lopez Chavez, Jose Humberto; Ortega Valerio, Victor Mario; Arrieta Barragan, Maria del Carmen (International Surgery Journal, 2025)
Keloids represent a complex pathological response to the wound healing process, characterized by an overgrowth of dermal fibrosis that exceeds the boundaries of the original wound. The auricle, particularly the earlobe, is a region of heightened susceptibility, owing to increased skin tension and frequent injury, most commonly resulting from ear piercing. The persistent nature of keloids, coupled with their high rate of recurrence, poses a significant therapeutic hurdle for medical professionals.